2016
DOI: 10.1002/pssr.201600060
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen on hybrid MoS2/graphene nanostructures

Abstract: Transition metal dichalcogenides are rising candidates for the replacement of Pt catalysts in water splitting. In this theoretical study we focus on the hydrogen evolution reaction part of this process and on how hydrogen (H) interacts with MoS2 nanostructures, free‐standing or positioned on a graphene substrate. Density functional theory calculations confirm the stability of such nanostructures and our results for H on several configurations, from 2D infinite monolayers to quasi‐1D MoS2 ribbons and quasi‐0D M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…For comparison with adsorption on the edges, we briefly summarize some of our results for the basal plane of monolayers, which are in overall agreement with literature, when available. [ 26,40,42,43 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison with adsorption on the edges, we briefly summarize some of our results for the basal plane of monolayers, which are in overall agreement with literature, when available. [ 26,40,42,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…For comparison with adsorption on the edges, we briefly summarize some of our results for the basal plane of monolayers, which are in overall agreement with literature, when available. [26,40,42,43] For atomic oxygen at full coverage, i.e., one O atom per X atom on one side of the MX 2 monolayer, we find that the adsorption energies for MoS 2 , WS 2 , MoSe 2 , WSe 2 are À0.27, À0.08, 0.81, 0.89 eV, respectively, showing that sulfides, unlike selenides, may be fully oxidized with O atoms adsorbed on top of S atoms.…”
Section: Adsorption Energeticsmentioning
confidence: 87%
See 1 more Smart Citation
“…Pan et al used the ultra-short gate lengths for ML-MoS 2 transistors to fabricate high-performance the short-gate MoS 2 transistors with high efficiency by conventional Si-based field-effect transistor with 0.7 nm monolayer CVD MoS 2 [26]. Since ML-MoS 2 has a strong SOC, one can combine graphene (with a weak SOC) and MoS 2 (with strong SOC) in a van der Waals heterostructure to obtain a controllable electric gate of the spin current and spin lifetime to obtain a high SOC material [27][28][29][30]. Niu investigates the valley-resolved thermoelectric transport through a magnetic silicene superlattice and demonstrates a strong valley polarization [31].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [20] found that armchair nanoribbons can be stabilized by H adsorption and possess a semiconducting character with strong exciton effects. Finally, Mos 2 nanoribbons could have a key role in the hydrogen evolution reaction [21,22], and graphene support enhances these features [23,24]. Yu et al [25] verified the tunability of edge states using electric field and hydrogen absorption.…”
Section: Introductionmentioning
confidence: 99%